Métodos analíticos para identificação e quantificação de espécies salinas e sedimentos em petróleo - Enders, Michele Stéfani Peters (2019)
In this work, the ASTM D 4807 standard method combined with scanning electron microscopy (SEM) was used and evaluated for the identification of the morphology and composition of saline species present in sediments isolated from emulsions of Brazilian pre-salt crude oils. Modifications to ASTM D 4807 were evaluated in order to assess the amount of isolated sediments and the solubility of the saline species present on the membrane surface. The evaluated modifications were: (I) mixture composed of 50% toluene + 50% isopropanol (v / v) as solvent; (II) mixture of 50% toluene + 49.5% isopropanol + 0.5% water as solvent and (III) additional membrane washing step with hot water after filtration following ASTM D 4807. For the sediment content determination, membranes with porosity of 0.10 and 0.22 μm were used. Additionally, the saline species retained on the membranes with porosity 0.45, 0.22 and 0.10 μm after filtration according to ASTM D 4807 were solubilized in water for further Ca, Cl, Mg and Na determination by ICP OES. Using SEM, different structures of inorganic solids were identified on the membrane surface post filtration according to ASTM D 4807, among which cubic, spherical, star, rod and finely divided solids can be highlighted. Regarding sediment composition, the elements Na, Cl, Ca, Ba Fe, K, Mg, S, Si and Sr were identified in the sediments retained on the nylon membranes. ASTM D 4807 with modification I produced a reduction (greater than 50%) of sediment content when compared to the method without modification. The toluene + isopropanol mixture possibly minimized the crystallization of some inorganic solids, as there is an increase in the solubility of chloride containing salts in isopropanol when compared to toluene. Modification I allowed the isolation of a larger amount of crystalline structures in the form of “salt spheres”. Apparently, the presence of these structures appears to be related to the presence of isopropanol in the solvent mixture used in the filtration. Regarding modification II, a reduction in sediment content was also observed. The use of water in the solvent mixture allowed the partial solubilization of part of inorganic solids otherwise insoluble (using the unmodified method or modification I). When modification III was used, a reduction of more than 82% in the amount of inorganic solids retained on the membrane surface was observed. This indicates that the additional washing step using hot water allows the solubilization of nearly all soluble inorganic species present in the sediment retained on nylon membranes. After washing with water, the presence of water-insoluble salts, probably composed of alkaline earth elements of sulfates and carbonates, iron and silicates was detected on the membrane surface. When membranes with smaller porosity (0.10 and 0.22 μm) were used, no significant difference in sediment content was observed for most samples when compared to the 0.45 μm membrane. Thus, some experimental conditions proposed by ASTM D 4807, especially the type of solvent used, induce crystallization of saline species present in petroleum emulsions. These species are probably soluble in the aqueous phase of the emulsions and the use of ASTM D 4807 with toluene originates these solid species, which are retained on the membrane surface. This conclusion is corroborated by the fact that modifications I, II and III allowed a reduction in sediment content.